Friendship and peer culture in multilingual settings - Theobald, Maryanne (Sociological studies of children and youth ;, 2016)
Authors of this book discover the intricacies of friendship and peer cultures of children in multilingual settings. Volume 21 brings together empirical research from across the globe, and from various methodological and theoretical orientations to investigate childrens relationships within multilingual settings such as school, home, community and online. Diverse views of children and young people on cross-cultural relationships offer rich and valuable findings and contribute new knowledge for policy makers, social workers, educators and parents about strategies children use to make friends.Internationally, the linguistic diversity of communities in the minority world is at its highest to date. With increasing numbers of children learning a language other than their home language at school or other places, it is important to understand the nature of the social relationships that children and youth are experiencing in their everyday lives in order to improve their chances of successful social experiences in the future. Applying a sociological perspective, this volume features the rich, varied and complex aspects of children's experiences of friendship in multilingual settings.